Antibiotic resistance patterns and therapeutic outcomes of pediatric Helicobacter pylori infection in a high‐migrant Singaporean cohort. Issue 1 (27th December 2021) - Huang, James Guoxian; Lim, Si Ying Sheryl; Aw, Marion Margaret; Quak, Seng‐Hock
Abstract: Background: Variation in Helicobacter pylori ( H . pylori ) disease in terms of prevalence and antibiotic resistance prevails globally requiring a need to develop region‐specific surveillance. We aimed to assess the influence of immigration factors upon the interpretation of local Singaporean epidemiological trends in antimicrobial susceptibility patterns and therapeutic outcomes in children with culture‐positive H . pylori . Materials and Methods: We retrospectively analyzed eradication outcomes of children with culture‐proven H . pylori infections between 2011 and 2020 at our center, and we also analyzed the antimicrobial susceptibility profiles of the corresponding H . pylori isolates. The cohort was classified into two groups: (1) Native Singaporeans and (2) Non‐native Singaporeans (First‐/Second‐generation immigrants and Non‐residents) to correlate with resistance patterns and eradication outcomes. H . pylori culture was done via Kirby‐Bauer disk diffusion for the era 2011–2016 and bioM é rieux E test for 2016–2020. Results: A total of 70 children (median age 14 [2–17] years) were included in the analysis. 42.9% (30/70) of the cohort displayed some form of antibiotic resistance; clarithromycin resistance was the most prevalent (30.0%), followed by metronidazole (27.5%) and amoxicillin (7.1%). Comparing to natives, non‐native Singaporeans were significantly younger at presentation (mean 11.7 vs. 13.7 years, p  = 0.043), and a significantly higher proportion of non‐natives carried clarithromycin‐resistant (51.4% vs. 8.6%, p  < 0.001), metronidazole‐resistant (47.1% vs. 8.6%, p  < 0.001), or multidrug‐resistant (resistant to ≥2 drugs) (40.0% vs. 2.9%, p  < 0.001] strains. Non‐natives were significantly more likely to fail first‐line eradication therapy (48.5% failure vs. 23.3%, p  = 0.038). The proportion of pan‐sensitive H . pylori was significantly lower in first‐generation (25.0%, p  = 0.001) and second‐generation (42.9%, p  = 0.018) immigrants compared to natives (82.86%). These conclusions did not vary when the analysis was repeated for each culture method. Conclusions: An antibiotic susceptibility‐based approach should be advocated for all patients but especially so for non‐natives, who are at higher risk for antimicrobial resistant strains and poorer eradication outcomes.